In vivo imaging reveals mature Oligodendrocyte division in adult Zebrafish - Zou, Suqi (Cell Regen, 2021)
Whether mature oligodendrocytes (mOLs) participate in remyelination has been disputed for several decades. Recently, some studies have shown that mOLs participate in remyelination by producing new sheaths. However, whether mOLs can produce new oligodendrocytes by asymmetric division has not been proven. Zebrafish is a perfect model to research remyelination compared to other species. In this study, optic nerve crushing did not induce local mOLs death. After optic nerve transplantation from olig2:eGFP fish to AB/WT fish, olig2(+) cells from the donor settled and rewrapped axons in the recipient. After identifying these rewrapping olig2(+) cells as mOLs at 3 months posttransplantation, in vivo imaging showed that olig2(+) cells proliferated. Additionally, in vivo imaging of new olig2(+) cell division from mOLs was also captured within the retina. Finally, fine visual function was renewed after the remyelination program was completed. In conclusion, our in vivo imaging results showed that new olig2(+) cells were born from mOLs by asymmetric division in adult zebrafish, which highlights the role of mOLs in the progression of remyelination in the mammalian CNS. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13619-021-00079-3.